Sex Dependent Dysregulation of Hepatic Glucose Production in Lean Type 2 Diabetic Rats - Blesson, Chellakkan S.; Schutt, Amy; Chacko, Shaji; Marini, Juan C.; Mathew, Pretty Rose; Tanchico, Daren; Balakrishnan, Meena; Yallampalli, Chandra (Frontiers in Endocrinology, 2019)
We have characterized a lean type 2 diabetic rat model by gestational low protein programming. We aimed to identify if the regulation of hepatic glucose production (HGP) via gluconeogenesis and glycogenolysis is affected and if there are any sex differences. Fasting (6-7 months old) type 2 diabetic rats received 2H2O followed by a primed constant rate infusion of [6,6-2H2] glucose. Blood samples were drawn during steady states after 4h of fasting and following a euglycemic hyperinsulinemic clamp. HGP and the fraction of glucose derived from gluconeogenesis under fasting and euglycemic states were measured from steady state glucose enrichments after the infusion of [6,6-2H2]glucose and 2H2O tracers. Glycogenolysis was determined by calculating the difference between total HGP and gluconeogenesis rates. Hepatic gene expression of enzymes involved in HGP were quantified using qPCR. HGP rates was similar during fasting in both groups and sexes. However, under simulated fed condition, HGP rate was suppressed in controls but not in type 2 diabetic rats. They also showed inefficient HGP suppression in a simulated fed state. Differential analysis showed that suppression of both gluconeogenesis and glycogenolysis under simulated fed state was affected in these low protein programmed type 2 diabetic rats. These effects were greater in females when compared to males. Further, key genes involved in these processes like G6Pase, Pepck, pyruvate carboxylase and glycogen phosphorylase in liver were dysregulated. Our data shows impaired suppression of HGP via gluconeogenesis and glycogenolysis in type 2 diabetic rats with greater effects on females.